Impact of a workplace holiday weight gain prevention program. Issue 3 (September 2019) - Wilson, Mark G; Padilla, Heather M; Meng, Lu; Daniel, Carmen N
Background: The average worker gains 2–3 lb (0.9–1.4 kg) a year, about half of which is gained during the fall holiday season (Halloween through New Year's). Aim: The aim of the study was to conduct a pilot test of a weight gain prevention program that was implemented in a workplace setting during the fall holiday season. Methods: 239 state government employees participated in a weight gain prevention program offered during the fall holiday season. The program was a 10-week, team-based program that consisted of self-monitoring, regular weigh-ins, a team challenge, and organizational support. Weight was measured at baseline, every two weeks during the program, and post-program. Results: Participants lost a significant amount of weight (from 196.7 lb/89.2 kg to 192.3 lb/87.2 kg) during the program. Positive changes were observed in physical activity and eating behaviors. Conclusions: This study demonstrated that a weight gain prevention program during a high risk period (fall holiday season) can be effective.